Entangled - Duda, Lidia (Poland : Kepińska, Anna, 2012)
A pedophile for over ten years and himself a victim of childhood sexual abuse, the abuser and the boys he molested live in the same small town, in a tight, messy knot of hatred, fear and emotional chaos. The roles of victim and aggressor became tragically reversed when one young man exacts revenge on his molester. The abuser becomes the abused in this complex and ambiguous struggle between crime and punishment, attempted murder and rape. The young man is put behind bars while his pedophile remains behind locked doors, fearing harassment from neighbors and his victim’s looming release date. Neither man regrets his crime, just its consequences. Entangled portrays a brutal grey area of blame, where both and neither are guilty. The filmmaker maintains a sensitive distance while filming the protagonists in their natural environments speaking openly about themselves.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films